Character animation fundamentals : developing skills for 2D and 3D character animation - Roberts, Steve, 1963- (Elsevier/Focal Press, 2011)
"Expand your animation toolkit and remain competitive in the industry with this leading resource for 2D and 3D character animation techniques. Apply the industry's best practices to your own workflows and develop 2D, 3D and hybrid characters with ease. With side by side comparisons of 2D and 3D character design, improve your character animation and master traditional principles and processes including weight and balance, timing and walks. Develop characters inspired by humans, birds, fish, snakes and four legged animals. Breathe life into your character and develop a characters personality with chapters on acting, voice-synching and facial expressions. Expertly integrate core animation techniques with your software of choice featuring step-by-step tutorials, highlighting 3ds Max, Maya and Blender workflows. Adapt the tips, tricks and techniques for unique projects like character design for rotoscoping and motion capture. Advance beyond the fundamentals of 2D and 3D character animation with the companion website which includes short demonstration movies, 2D and 3D exercises and fully rigged character models. Enhance your 2D skillset to the benefit of your own 3D animations to develop characters that technically and artistically dynamic and engaging. Expand your Animation toolset and resume while learning how to develop and design 2D and 3D characters with ease with side by side comparisons of 2D and 3D walk cycles, timing, balance and facial expressions. Includes practical, hands-on examples, step by step tutorials, now fully updated to include 3ds Max, Maya and Blender tutorials. Explore the new trends in character animation with new content on motion capture and rotoscopy character design and master the fundamental techniques with the companion website which includes short demonstrations, 2D and 3D exercises and 20 fully rigged character models."
Obsahuje rejstřík
Keywords: počítačová animace; 3D Studio MAX (software); Maya (software); filmová animace; computer animation; 3D Studio MAX; film animation; příručky; handbooks, manuals, etc